Kekerasan Kolektif di Perkotaan: Konstruksi dan Representasi Maskulinitas dalam Budaya Masyarakat Makassar - Muhammad - Syaiful (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2017)
The occurrence of violence in South Sulawesi whereever they are, they are usually identified as violence that happen in Makassar. This is due to the fact the frequent of violence happen in Makassar than in other cities in Indonesia. This article aims to explore collective violence in two adjoining locations in Makassar, yakni Pampang dan Sukaria and how this is related to masculinity. The pattern of collective violence between people in both areas based on classification and motivesof conflict between groups. The motive of collective violence, namely yakni seizure of land, this then develop mass coordination established through the process of patronage relations and the formation of strong lokal men. This then lead to establishment of routine violence which hands in hand in hand with siri’ na pacce. The construction of masculinity from male perspective that women are obliged to maintain such values through violent ways. Parenting pattern tends to be permissive towards violence. Such violence is common among male members of society. This violence has become an expression of masculinity. Masculinity is symbolised through four aspects: badik, bow arrow, tatto’ dan ballo (a local drink). Thus, one who can performs these aspects will be considered as rewa.